Respuesta :
ok, so seems to be geometric
an=a1(r)^(n-1)
a1=first term
r=commonr atio
n=number of term
first term is -4
common ratio is -16/-4=4
so
a1=-4
r=4
[tex]a_n=-4(4)^{n-1}[/tex]
D is the answer
an=a1(r)^(n-1)
a1=first term
r=commonr atio
n=number of term
first term is -4
common ratio is -16/-4=4
so
a1=-4
r=4
[tex]a_n=-4(4)^{n-1}[/tex]
D is the answer
The nth term of the sequence is [tex]a_n= -4(4)^{n-1}[/tex]. Option D is correct.
What is geometric progression?
When there is a constant between the two successive numbers in the series then it is called a geometric series.
The formula for finding the nth term is,
[tex]a_n = a(r)^{n-1}[/tex]
Given series is -4, -16, -64, -256, ...
a₁ = -4 and r = -16 / -4 = 4
The nth term will be calculated as:-
[tex]a_n = -4(4)^{n-1}[/tex]
Therefore, the nth term of the sequence is [tex]a_n= -4(4)^{n-1}[/tex]. Option D is correct.
To know more about geometric progression follow
https://brainly.com/question/12006112
#SPJ2